Biological, Physical, and Atmospheric Controls on the Distribution of Cadmium and Its Isotopes in the Pacific Ocean. Issue 2 (27th January 2023) - Sieber, Matthias; Lanning, Nathan T.; Bunnell, Zachary B.; Bian, Xiaopeng; Yang, Shun‐Chung; Marsay, Chris M.; Landing, William M.; Buck, Clifton S.; Fitzsimmons, Jessica N.; John, Seth G.; Conway, Tim M.
Abstract: Despite the Pacific being the location of the earliest seawater Cd studies, the processes which control Cd distributions in this region remain incompletely understood, largely due to the sparsity of data. Here, we present dissolved Cd and δ 114 Cd data from the US GEOTRACES GP15 meridional transect along 152°W from the Alaskan margin to the equatorial Pacific. Our examination of this region's surface ocean Cd isotope systematics is consistent with previous observations, showing a stark disparity between northern Cd‐rich high‐nutrient low‐chlorophyll waters and Cd‐depleted waters of the subtropical and equatorial Pacific. Away from the margin, an open system model ably describes data in Cd‐depleted surface waters, but atmospheric inputs of isotopically light Cd likely play an important role in setting surface Cd isotope ratios (δ 114 Cd) at the lowest Cd concentrations. Below the surface, Southern Ocean processes and water mass mixing are the dominant control on Pacific Cd and δ 114 Cd distributions. Cd‐depleted Antarctic Intermediate Water has a far‐reaching effect on North Pacific intermediate waters as far as 47°N, contrasting with northern‐sourced Cd signatures in North Pacific Intermediate Water. Finally, we show that the previously identified negative Cd* signal at depth in the North Pacific is associated with the PO4 maximum and is thus a consequence of an integrated regeneration signal of Cd and PO4 at a slightly lower Cd:P ratio than the deep ocean ratio (0.35 mmol mol −1 ), rather than being related to in situ removal processes in low‐oxygen waters. Key Points: Atmospheric inputs of isotopically light Cd play an important role in setting surface δ 114 Cd when surface Cd concentrations are low Strong Southern Ocean control on subsurface Cd and δ 114 Cd distribution; Antarctic Intermediate Water influences δ 114 Cd of North Pacific intermediate waters A Cd* minimum at depth in the North Pacific is associated with the PO4 maximum, a consequence of integrated regeneration